2020
DOI: 10.1186/s12967-020-02545-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a robust immune-related prognostic signature in early-stage lung adenocarcinoma

Abstract: Background The incidence of stage I and stage II lung adenocarcinoma (LUAD) is likely to increase with the introduction of annual screening programs for high-risk individuals. We aimed to identify a reliable prognostic signature with immune-related genes that can predict prognosis and help making individualized management for patients with early-stage LUAD. Methods The public LUAD cohorts were obtained from the large-scale databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…Consistent with these findings, the patients in gene cluster A exhibit better prognosis than gene cluster B and C. The anti-cancer immune response in gene cluster A is associated with favorable prognosis and we believe that the patients in gene cluster A may benefit from immunotherapy. In order to identify the role of higher immune cell infiltration in improving patient survival, the GSEA analysis was performed, and the results showed that the immunological response-related pathways have been well activated, such as pathways related to positive regulation of cytokine production ( Giles et al, 2018 ; Fisher et al, 2019 ), regulation of immune effector process ( Wu et al, 2020b ), and leukocyte proliferation ( MollicaPoeta et al, 2019 ). And the relative biomarker expression of cytokines also confirmed this result.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, the patients in gene cluster A exhibit better prognosis than gene cluster B and C. The anti-cancer immune response in gene cluster A is associated with favorable prognosis and we believe that the patients in gene cluster A may benefit from immunotherapy. In order to identify the role of higher immune cell infiltration in improving patient survival, the GSEA analysis was performed, and the results showed that the immunological response-related pathways have been well activated, such as pathways related to positive regulation of cytokine production ( Giles et al, 2018 ; Fisher et al, 2019 ), regulation of immune effector process ( Wu et al, 2020b ), and leukocyte proliferation ( MollicaPoeta et al, 2019 ). And the relative biomarker expression of cytokines also confirmed this result.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these ndings, the patients in gene cluster A exhibits the better prognosis than gene cluster B and C. The anti-cancer immune response in gene cluster A is associated with favorable prognosis and we believed that the patients in gene cluster A may bene t from the immunotherapy. In order to identify the role of higher immune cell in ltration in improving the patient survival, the GSEA analysis was performed and the results showed that the immunological response-related pathways have been well activated, such as pathway related to positive regulation of cytokine production [33][34] , regulation of immune effector process 35 , leukocyte proliferation 36 etc. And, the relative biomarker expression of cytokines also con rmed this result.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in 2020, Liang et al also proposed a promising 21-gene-based prognostic immune prediction model for early-stage LUAD patients in the TCGA cohort. 52 The C-index, a frequently utilized evaluation indicator for survival models, was estimated through "pec" R package utilizing a bootstrap manner under 1000 resampling, thus comparing the predictive performance of the previously published prognostic signatures and our IPM. A higher C-index value indicates the more favorable predictive performance of the model.…”
Section: Geo Cohortmentioning
confidence: 99%